The Appropriate Bargaining Unit: The Need for Policy Consistency by Canadian Labour Boards - McPhillips, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
This paper discusses the policies of the Boards with regard to administrative changes, consolidations, accretions, mergers, partial raids and partial decertifications.